Analyzing the Russian-Ukrainian War Through Ethnic Conflict Theories - Gul, Mehreen; Khan, Imran (Jisiera: The Journal of Islamic Studies and International Relations, 2025)
Since 2014, Russia and Ukraine have been locked in a protracted conflict in Eastern Ukraine, escalating in the Russian invasion of Ukraine in 2022. Both sides utilized various ethnically charged propaganda themes to justify their positions. This paper examines the extent to which the conflict is framed as an indispensable necessity to protect the ethnic interests of Ukraine and Russia. The paper employs the three ethnic theories—primordialism, constructivism, and instrumentalism—to analyze the underlying dynamics of the ethnic propaganda in the Russia-Ukrainian conflict. The finding suggests that the broader geopolitical interests are veiled in the ethnic narratives from both sides.